ANALISIS PERUBAHAN TUTUPAN LAHAN KOTA LUBUK PAKAM ANTARA TAHUN 2012 DENGAN 2015 - Sugiatno Sugiatno; Anita Zaitunah; Samsuri Samsuri (Program studi Kehutanan USU, 2016)
The development of city and the increasing number of people has become a problem, especially the decreasing of forest city land caused by the construction and development process which have been done without considering the surrounding environment. This research aims to find out the changes of land cover in the district of Lubuk Pakam between 2012 and 2015. The Classification of land cover used Landsat 7 and Landsat imagery 8 OLI. The Classification of land cover was done using supervised classification and North Sumatera’s monogram. This research showed the change of land cover between 2012 and 2015. There are decrease of some areas which are 1,58% of are paddy field, 0,57% of dry land agriculture, 0,07% of shrub and 0,14% of bare land. But there is an increase of settlement areas which is 2,36% of the area. Keywords: Land Coverage Change, Lubuk Pakam City, Image Interpretation, Landsat Imagery.